State and Citizen Roles in Budget Deficit Management: A Systematic Literature Review - Putra Kristianto, Fesa; Shoffiyati, Peni; Prakoso, Galih (Banking & Management Review, 2025)
Background Problems: Managing state budget deficits is crucial for fiscal sustainability, particularly in emerging economies like Indonesia. Despite existing fiscal policies, gaps remain in their implementation, compounded by issues like low tax compliance, inefficient spending, and external economic shocks. Introduction/Main Objectives: This study investigated the role of the state and citizens in managing the budget deficit, with a focus on Indonesia's fiscal policy and the importance of public engagement in addressing fiscal challenges. Novelty: This research introduces a novel approach by incorporating citizen participation into fiscal deficit management, an aspect often overlooked in traditional fiscal policy frameworks. It emphasizes the role of public involvement in enhancing fiscal discipline, transparency, and accountability. Research Methods: A systematic literature review (SLR) was employed to synthesize studies on fiscal policy, budget management, and public participation. The review identifies best practices from both domestic and international contexts for managing fiscal deficits. Findings/Results: Key strategies for managing Indonesia’s budget deficit include enforcing balanced budget policies, controlling expenditures, and utilizing fiscal reserves. The study highlights the crucial role of citizens in supporting these strategies through engagement in policy discussions, oversight of public spending, and promoting tax compliance. Conclusion: The study concludes that sustainable fiscal management requires a combination of technical policy reforms and active citizen participation. Public involvement in fiscal governance can improve transparency and enhance the effectiveness of deficit management, fostering long-term economic stability.